Pengaruh Latihan Modifikasi Fisik Terhadap Perkembangan Motorik Kasar Anak Usia 5 – 6 Tahun di TK Al – Ikhlas Mekar Jaya - Rika Rina Nainggolan; Sukendro Sukendro; Sri Indriani Harianja (Journal of Innovative and Creativity (Joecy), 2026)
Gross motor development is the process of children learning to control and coordinate the large muscles of the body so that they are able to move with strength, balance, agility, flexibility, and good coordination. The results of initial observations at Al-Ikhlas Mekar Jaya Kindergarten showed that the gross motor skills of children aged 5–6 years had not developed optimally, because learning focused more on reading, writing, and arithmetic activities with minimal physical activity. This study aims to determine the effect of physical modification exercises on the gross motor development of children aged 5–6 years at Al-Ikhlas Mekar Jaya Kindergarten. This study used a quantitative method with a One-Group Pretest-Posttest Design. The research sample consisted of 14 class B1 children selected using a purposive sampling technique. The study was conducted for 7 weeks with 1 pretest, 16 treatments, and 1 posttest. The treatment was given through four games, namely frog jumping, walking on a bridge, zigzag running, and throwing and catching a ball, which were designed to train strength, balance, agility, flexibility, and coordination. Data collection was conducted through observation using a checklist containing 10 statements with a four-level rating scale. The results showed a significant improvement in children's gross motor development, with an average pretest score of 20.64 increasing to 36.71 in the posttest, representing a difference of 16.07 points. A paired sample t-test yielded a significance value of 0.000 ≥0.05, thus rejecting H₀ and accepting Hₐ. Cohen's d effect size was 5.94, categorizing it as a strong effect. Therefore, it can be concluded that physical modification exercises significantly influence the gross motor development of children aged 5–6 years at Al-Ikhlas Mekar Jaya Kindergarten.